The Widening Gap in Basic Education: A Brief Overview - Paul A. Wagner (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
News media often suggest that schools are not teaching practical skills. Depending on the story the practical skills named include balancing a check book, maintenance of proper hygiene, finding public and social services, avoiding pollution, how best to re-cycle materials and even how to change diapers. Despite claims that education is not addressing basic education and so-called life skills, such claims must be weighed against what various constituencies count as basic and more so, life-skills. Most decidedly the inclusion of instruction first in natural frequency evaluation and then in Bayesian reasoning is critical as Gigerenzer and coauthors have shown in “The Foundations of Adaptive Behavior” in 2015. Certainly, there is a cost to the inclusion of any material especially as proposed herein. But the cost when it leads to more effective evaluations of truth across the curriculum is worth it considering the “Law of Figuring it Out, LFTO as proposed by Paul A. Wagner in “Thinking Ahead: Engaging All Teachers in Critical Thinking” in 2018. This study explains why Gigerenzer’s focus on statistical reasoning across the curriculum advances the concept behind a generalized commitment to evaluative reasoning as is proposed in the LFTO. The sketch to follow proposes that the fourth “r” reasoning includes instruction in statistical thinking to make all students more mindful of LFTO practices when seeking understanding rather than mere recollection skills. Modification of material in mathematics, social studies, science, and where it exists, philosophy for children, can emphasize the importance of justification as indispensable to genuine insight.